The Influence of the School Environment on the Formation of Primary School Students’ Character - Nabila Nurul Laila (International Journal of Students Education, 2024)
Environment school is realm education second for participant educate. In the environment school participant educate guided in all aspects, morals, knowledge and skills is something very important thing for built in environment school. The problem is, what? there is influence between environment school to formation character student at school basic and presumptive that there is positive influence between environment school to formation character student. This study aims to see how the school environment influences the formation of student character in elementary schools. Study This expected can beneficial in development knowledge, improvement and reference for researchers, teachers, and head school in carrying out education in the future. Method used in this study is study literature (library research). This study using secondary data form journal scientific, results study as well as books and other relevant sources. Literature or library used in this study is books, articles journals, proceedings, and reports study as listed in the bibliography. Data analysis techniques used covers three stages that is organizing, synthesizing, and identifying. Research result this show that the school environment has a significant influence on the formation of student character. With thereby education character must noticed especially in room scope school so that can embedded in self student as shield and provisions in act as well as can formed generation that has good character. Therefore, teachers and parents must play an active role in making it happen.